2022
DOI: 10.3892/ol.2022.13352
|View full text |Cite
|
Sign up to set email alerts
|

Cancer stem cell marker expression and methylation status in patients with colorectal cancer

Abstract: The number of individuals diagnosed with colorectal cancer (CRC) has been on an alarming upward trajectory over the past decade. In some countries, this cancer represents one of the most frequently diagnosed types of neoplasia. Therefore, it is an important demand to study the pathology underlying this disease to gain insights into the mechanism of resistance to treatment. Resistance of tumors to chemotherapy and tumor aggressiveness have been associated with a minor population of neoplastic cells, which are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…The number of individuals diagnosed with colorectal cancer (CRC) has been on an alarming upward trajectory over the past decade. In some countries, this cancer represents one of the most frequently diagnosed types of neoplasia (4). It had been estimated that in 2020, the incidence and mortality rates of colorectal cancer would increase by more than 1.9 million cases and 930,000 deaths, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The number of individuals diagnosed with colorectal cancer (CRC) has been on an alarming upward trajectory over the past decade. In some countries, this cancer represents one of the most frequently diagnosed types of neoplasia (4). It had been estimated that in 2020, the incidence and mortality rates of colorectal cancer would increase by more than 1.9 million cases and 930,000 deaths, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…A disintegrin and metalloproteinase domain with thrombospondin motifs 16 (ADAMTS16) belongs to the ADAMTS family. Its role has been investigated in esophageal squamous cell carcinoma ( 14 ) and CRC ( 15 , 16 ). However, to the best of our knowledge, the role of ADAMTS16 in HCC has not yet been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Cakmak et al reported that ADAMTS16 was downregulated in a chondrosarcoma cell [ 11 ]. In colorectal cancer (CRC), ADAMTS16 was hypermethylated and high expression of ADAMTS16 restrained cancer cell proliferation [ 9 , 13 ]. Meanwhile, the mutation of ADAMTS16 altered the sensibility of ovarian cancer to platinum-based chemotherapy [ 10 ].…”
Section: Introductionmentioning
confidence: 99%